IMPLEMENTASI SISTEM PEMETAAN LOKASI STOK DARAH BERBASIS ANDROID MENGGUNAKAN METODE LOCATION BASED SERVICE DI BENGKULU - Jaswan, Mali; Yulianti, Liza; sapri, sapri (Jurnal Media Infotama, 2022)
ABSTRAC Blood donation is the process of voluntarily giving blood for the purpose and purpose of blood transfusion for other people in need. The process of delivering information related to blood stock, the public must always visit PMI, so it is inefficient and less effective. Many want to stock up blood to help others, but because of the lack of information, people don't know how to find out the location of existing blood stocks. The result of this research is a blood stock application that is able to provide blood bag stock data, as well as blood stock information. This makes it easier for users to find information about the method, place, and requirements for blood stock so that it is hoped that the public (users) who need blood supply information can access accurate and reliable information that has been presented by the PMI or UTD concerned. Keywords: blood stock, PMI, android, application